2016
DOI: 10.1186/s40360-016-0092-7
|View full text |Cite
|
Sign up to set email alerts
|

National study on the adequacy of antidotes stocking in Lebanese hospitals providing emergency care

Abstract: BackgroundAntidotes stocking is a critical component of hospital care for poisoned patients in emergency. Antidote stocking represents a major health challenge worldwide and in Lebanon. Systematic data monitoring of antidote stocking in Lebanese hospitals is lacking. The objective of this study is to assess the adequacy of antidotes stocking in Lebanese hospitals according to type and quantity and explore the characteristics associated with their differential availability.MethodsData collection to assess antid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Although adequate measures are available in most developed countries to combat poisoning when reported early, more efficient methods of dissemination and administration of these antidotes are also under appraised. Studies, however, revealed inadequate stocking [5,6,[20][21][22] and in some cases, absence of some essential antidotes [4] as major hindrances. This is in sharp contrast to the experience in most rural areas and developing countries where antidotes are hardly available, leaving them with the only option of herbal antidotes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although adequate measures are available in most developed countries to combat poisoning when reported early, more efficient methods of dissemination and administration of these antidotes are also under appraised. Studies, however, revealed inadequate stocking [5,6,[20][21][22] and in some cases, absence of some essential antidotes [4] as major hindrances. This is in sharp contrast to the experience in most rural areas and developing countries where antidotes are hardly available, leaving them with the only option of herbal antidotes.…”
Section: Discussionmentioning
confidence: 99%
“…However, relevant antisera not being stocked and in insufficient amounts remains a daunting problem. This problem has been repeatedly documented for a range of antidotes in many developed nations, including the United Kingdom (UK), Canada, the US [20,21], Qatar [22] and Korea [5].…”
Section: Introductionmentioning
confidence: 99%
“…Buckley and colleagues note the availability of more emergency departments, postgraduate training in toxicology, updated treatment guidelines, and wider availability of antidotes in Sri Lanka over the study period. 3 Data from several lowincome countries highlight the limited and variable availability of treatment resources for managing poisoning, 8,9 flagging the potential for improvements in care alongside pesticide regulation in averting deaths from pesticides.…”
Section: Pesticide Surveillance and Deaths By Suicidementioning
confidence: 99%
“…Unfortunately, the stocking of antidotes has been a “persistent concern” for over 35 years [ 1 ]. Countries have conducted regular audits on antidotes stocking, and many researchers have recommended the development of a national list and stocking guidelines to standardize care [ 4 , 6 , 7 ]. A globally recognized consensus guideline recommended a “list” of antidotes to be stocked for timely delivery of essential antidotes to the emergency department [ 1 ].…”
Section: Introductionmentioning
confidence: 99%